2013
DOI: 10.1016/j.neuroimage.2013.04.103
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted directed connectivity along the cingulate cortex determines vigilance after sleep deprivation

Abstract: The cingulate cortex is regarded as the backbone of structural and functional connectivity of the brain. While its functional connectivity has been intensively studied, little is known about its effective connectivity, its modulation by behavioral states, and its involvement in cognitive performance. Given their previously reported effects on cingulate functional connectivity, we investigated how eye-closure and sleep deprivation changed cingulate effective connectivity, estimated from resting-state high-densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 118 publications
(186 reference statements)
4
19
0
Order By: Relevance
“…1a, b) is in line with previous findings that reported EO connectivity in the forward direction to be greater compared to EC [2]. As a caveat, there are differences between the present article and the findings of Piantoni et al [2], specifically the frequency range, algorithm used for computing connectivity, and the number and location of the estimated sources. Nonetheless, the authors believe the pattern that emerged in the present study is consistent with the discovery presented in their report.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…1a, b) is in line with previous findings that reported EO connectivity in the forward direction to be greater compared to EC [2]. As a caveat, there are differences between the present article and the findings of Piantoni et al [2], specifically the frequency range, algorithm used for computing connectivity, and the number and location of the estimated sources. Nonetheless, the authors believe the pattern that emerged in the present study is consistent with the discovery presented in their report.…”
Section: Discussionsupporting
confidence: 89%
“…Figure 1b illustrates the significant increase in feedforward connectivity under EO as compared to EC. An increase of feedforward connectivity by comparing EC with respect with EO was also found in a previous study [2]. …”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…It has been demonstrated that sleep loss can reduce performance on a broad variety of tasks and affects brain functional activity [7,8]. Nevertheless, no previous study has examined the effects of sleep loss on gray matter (GM) structures in healthy adults.…”
Section: Introductionmentioning
confidence: 99%